Identification of antibodies cross-reactive with woodchuck immune cells and activation of virus-specific and global cytotoxic T cell responses by anti-PD-1 and anti-PD-L1 in experimental chronic hepatitis B and persistent occult hepadnaviral infection - Corkum, Christopher P.; Wiede, Louisa L.; Ruble, Cara L.-A.; Qiu, Jiabin; Mulrooney-Cousins, Patricia M.; Steeves, Meredith A.; Watson, David E.; Michalak, Tomasz I. (Frontiers in Microbiology, 2022)
Woodchuck (Marmota monax) infected with woodchuck hepatitis virus (WHV) is the most pathogenically compatible naturally occurring model of human hepatitis B virus (HBV) infection, chronic hepatitis B, and HBV-induced hepatocellular carcinoma. This system plays a crucial role in discovery and preclinical evaluation of anti-HBV therapies. Its utilization remains tempered by the relatively narrow range of validated immunologic and molecular tools. We evaluated commercial antibodies against immune cell phenotypic markers and T cell molecules for cross-reactivity with woodchuck antigenic equivalents. The confirmed antibodies against programed cell death protein-1 (PD-1) and its ligand (PD-L1) were examined for ex vivo ability to activate WHV-specific and global cytotoxic T cells (CTLs) in chronic hepatitis and asymptomatic infection persisting after self-resolved acute hepatitis. Examination of 65 antibodies led to identification or confirmation of 23 recognizing woodchuck T, regulatory T, B and natural killer cells, T cell-associated PD-1, PD-L1, CTLA-4 and TIM-3 molecules, CD25 and CD69 markers of T cell activation, and interferon gamma (IFNγ). Antibodies against woodchuck PD-1 and PD-L1 triggered in vitro highly individualized WHV-specific and global activation of CTLs in both chronic hepatitis and persistent occult infection. WHV-specific CTLs were more robustly augmented by anti-PD-1 than by anti-PD-L1 in chronic hepatitis, while global IFNγ-positive CTL response was significantly suppressed in chronic hepatitis compared to persistent occult infection. Anti-PD-1 and anti-PD-L1 also occasionally activated CTLs to specificities other than those tested suggesting their potency to trigger side effects. This was particularly apparent when T cells from chronic hepatitis were treated with anti-PD-L1. The current findings indicate that inhibition of the PD-1/PD-L1 pathway could reactivate virus-specific and global T cell responses in both chronic hepatitis and asymptomatic persistent infection. They suggest a mechanism of potential reactivation of clinically silent infection during anti-PD-1/PD-L1 treatment and indicate that this therapy may also subdue occult HBV infection.